Formulation and Pharmaceutical Evaluation of Capsules Containing the n-Hexane Fraction of Moringa oleifera Leaves - Mathias, Sylvester Nefai; Ahmed, Aliyu Hamidu; Mshelia, Emmanuel Halilu; Mohammed, Achor; Ugwah-Oguejiofor, Chinenye Jane; Lawal, Mansur; Alkali, Ibrahim Yusuf; Igbokwe, Nkeiruka Nkeonyere; Ukwubile, Cletus Anes; Biambo, Ahmed Aminu (Sciences of Phytochemistry, 2026)
This study investigated the phytochemical composition, safety profile, and pharmaceutical formulation of capsules containing the hexane fraction of Moringa oleifera leaves (MOHx). The main objective of this study was to comprehensively evaluate the phytochemical constituents, toxicity profile, and develop a standardized oral capsule formulation of the hexane fraction of M. oleifera leaves suitable for potential therapeutic application. Phytochemical profiling was performed using LC–MS and GC–MS, and compounds were tentatively identified based on spectral library matching and fragmentation patterns. Selected phytochemicals were evaluated using in silico ADMET prediction and molecular docking analyses. Acute oral toxicity was assessed in Wistar rats using Lorke’s method. Pre-formulation studies were conducted prior to capsule formulation using the wet granulation technique. The granules were evaluated for micromeritic properties, and the capsules were subjected to pharmacopoeial quality tests including weight uniformity, disintegration, and dissolution. The estimated LD₅₀ of the extract was 3.808 mg/kg body weight, indicating relatively low acute toxicity. Dissolution testing showed more than 80% release within 20 min under the experimental conditions employed. These findings suggest that the developed capsule formulation provides a suitable pharmaceutical dosage form for the hexane fraction of M. oleifera, although further studies including stability testing, quantitative phytochemical standardization, and pharmacological evaluation are required.